The math explorer : a journey through the beauty of mathematics - Weaver, Jefferson Hane. (Hyderabad Prometheus Books, 2007)
This stress-free layperson's introduction to the intriguing world of numbers is designed to acquaint the general reader with the elegance and wonder of mathematics. Unlike the typical boot-camp experience of a high school or college calculus course, Jefferson Hane Weaver's approach is more like a relaxing and educational walking tour. Along the way, tour-guide Weaver points out, explains, and invites readers to sample some of the most interesting topics. Even the most math-phobic among us will be lulled into appreciation by Weaver's creative and disarming discussions of this supposedly formidable intellectual discipline. He covers all the basics: irrational and imaginary numbers, algebra, geometry, trigonometry, differential and integral calculus, the concepts of zero and infinity, vectors, set theory, chance and probability, and much more. In conclusion, he provides five fascinating historical profiles, reviewing the life and work of Copernicus, Descartes, Kepler, Galileo, and Newton. More than anyone else, these five geniuses were responsible for creating the mathematical foundations of the physical sciences, which continue to make possible extraordinary discoveries and technological achievements. This enjoyable volume gives readers a working knowledge of math's most important concepts, an appreciation of its elegant logical structure, and an understanding of its historical significance in creating our contemporary world.